Mechanistic insight into enzymatic glycosyl transfer with retention of configuration through analysis of glycomimetic inhibitors. - Errey, J; Lee, S; Gibson, R; Martinez Fleites, C; Barry, C; Jung, P; O'Sullivan, A; Davis, B; Davies, G (2010)
(Figure Presented) Structural "valid"-ation: The mechanism of enzyme-catalyzed glycosyl transfer with retention of anomeric configuration continues to baffle, a situation compounded by the lack of insightful 3-D structures of ternary enzyme complexes. Synthesis and multi-dimensional kinetic analysis of validoxylamine derivatives are used to access the 3-D structure of a ternary complex (see picture; U = uridyl) providing insight into the geometry and donor-acceptor interplay at the glycosyltransfer site. © 2010 Wiley-VCH Verlag GmbH and. Co. KGaA.